3x - 1y = 5
x = -2
Keep in mind that the "1" in front of the y is redundant, and we can remove it.
3x - y = 5
x = -2
What we want to do is solve for x and y. But we already have
x = -2, so all we need to do is solve for y. Plug in x = -2 into the first equation to solve for y.
3x - y = 5.
Substitute x = -2, to get
3(-2) - y = 5
Multiply 3 and -2, to get
-6 - y = 5
Move the -6 over to the right hand side to make it +6, to obtain
-y = 5 + 6
Simplify,
-y = 11
Now, multiply both sides by -1, to get rid of the negative sign in front of the y.
y = -11
So your answer is
x = -2
y = -11
2007-01-01 09:49:06
·
answer #1
·
answered by Puggy 7
·
1⤊
0⤋
Substitute -2 for x in the first equation:
3 * (-2) -1y = 5
-6 -y = 5
-y = 5 + 6
y = -11
2007-01-01 17:48:24
·
answer #2
·
answered by hznfrst 6
·
0⤊
0⤋
3x-1y=5, you dont need the one in front of y because it is implied that there is a one there if no other number is provided. (the work 'too', go back and learn grammar as well)
x=-2
3(-2) - 1y =5
substitute -2 for x
-6-y=5
+6 +6
add 6 to both sides
-y=11
/-1 /-1
divide 11 by -1
answer is y= -11
/ -this symbol means divide by
do your own homeowrk for petes sake, damn
2007-01-01 18:03:04
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
3(-2) - y = 5
-6 - y = 5
-y = 5 + 6 by adding 6 to both sides
-y = 11 now divide by -1
y = -11
2007-01-01 17:47:10
·
answer #4
·
answered by Professor Maddie 4
·
0⤊
0⤋
3x-1y=5,
x=-2 substitute
3(-2)-y=5
-6-y=5 add 6 to each side
-y=11 divide by -1
y=-11
(-2, -11)
2007-01-01 18:26:05
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
3(-2)-1y=5
-6 - y = 5
-y = 5 + 6
y = -5 -6
y = -11
Solution: {(-2; -11)}
<><>
2007-01-01 18:11:41
·
answer #6
·
answered by aeiou 7
·
0⤊
0⤋
sub -2 for x
3(-2)-1y=5
-6-1y=5
-1y=11
y= -11
2007-01-01 17:48:35
·
answer #7
·
answered by 7
·
0⤊
0⤋
3*-2 - y = 5
-6 -y = 5
y = -6 -5
y = -11
2007-01-01 17:48:50
·
answer #8
·
answered by M. Abuhelwa 5
·
0⤊
0⤋